Phonon Dynamics and Acoustic and Thermodynamic Properties of Pt57.5Cu14.7Ni5.3P22.5 Bulk Metallic Glass - koireng, R. R.; Agarwal, P. C.; Gokhroo, A. (Journal of Scientific Research, 2021)
The phonon dispersion curves for Pt57.5Cu14.7Ni5.3P22.5 bulk metallic glass (BMG) are computed employing various dielectric screenings using the simple model given by Bhatia and Singh. The force constants β and δ for computing the dispersion curves are calculated from the elastic constants i.e. bulk modulus (B) and shear modulus (G) along with the calculated value of force constant κe of the material of the glass for the first time. The results of the phonon dispersion curves show appropriate behavior in the long wavelength region in detail for both the longitudinal and transverse modes and give insight regarding the acoustic and thermal properties of the BMG. The transverse sound velocity and the longitudinal velocities with various dielectric screening are calculated from the dispersion curves in the long wavelength region. The corresponding thermodynamic property (Debye temperature) is calculated for different dielectric screenings. The theoretical results predicted are in a good agreement with the reported data in the literature for the Pt57.5Cu14.7Ni5.3P22.5 BMG and may be used for correlating other properties.